2013
DOI: 10.1097/iop.0b013e31828de0b0
|View full text |Cite
|
Sign up to set email alerts
|

The Narrowest Part of the Bony Nasolacrimal Canal

Abstract: The shortest anteroposterior and transverse diameters were at the entrance of the canal in most of the bony nasolacrimal canals. These results are comparable with the rate of obstruction at the canal entrance in primary acquired nasolacrimal duct obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 14 publications
1
25
1
Order By: Relevance
“…The measurements of the NLD bone in our study are smaller than reported in the literature in several populations, such as Asians and Africans (Saxena; Janssen et al; Shigeta et al;McCormick & Sloan;Fasina & Ogbole;Takahashi et al, 2011Takahashi et al, , 2013Yong et al) that showed greater diameters than those found in our population (Table III). Our study in Mexican population reports values that tend to be smaller than those of other populations, so we believe that there are differences in the NLD between ethnic groups (Table III), which could explain differences between countries in prevalence of lower nasolacrimal duct obstruction in adults.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…The measurements of the NLD bone in our study are smaller than reported in the literature in several populations, such as Asians and Africans (Saxena; Janssen et al; Shigeta et al;McCormick & Sloan;Fasina & Ogbole;Takahashi et al, 2011Takahashi et al, , 2013Yong et al) that showed greater diameters than those found in our population (Table III). Our study in Mexican population reports values that tend to be smaller than those of other populations, so we believe that there are differences in the NLD between ethnic groups (Table III), which could explain differences between countries in prevalence of lower nasolacrimal duct obstruction in adults.…”
Section: Discussioncontrasting
confidence: 56%
“…Several authors show length differences of the bone entrance of the NLD that might be related to ethnic or methodological differences (Table III) Takahashi et al, 2011Takahashi et al, , 2013Yong et al).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average distance of the point with narrowest caliber from the superior opening was 3.33 ± 1.48 mm (0.0-7.16 mm) and, in only one case, it was at the superior opening of the canal, while in Japanese cadavers, in 32 of 44 canals (72.7%) it was at the entrance to the canal and, in the rest, it was located at an average of 3.6 mm from the entrance. 12 Groell et al 17 reported it to be located in the middle or upper part of the canal, while Groessl et al 18 showed that the narrowest point was located 3 mm inferior to the canal entrance. All these are comparable with our study.…”
Section: Discussionmentioning
confidence: 98%